Joseph Bologne in an Atlantic View - Koslowski, Kaleb (Alternative francophone, 2025)
Joseph Bologne, the Chevalier de Saint-George, has been an important historical figure for musicologists. When he entered music-historical conversations in the 1990s, his charismatic persona and, especially, his Blackness opened the door to discussions about how Black and mixed-race musicians had contributed to European music cultures before 1800, and drew important attention to the ways they were passed over in scholarship. Many of those conversations and many since, however, have focused on Bologne and his Blackness as exceptional, as a historical curiosity. Although effective as a critical tool, this exceptionality has monumentalized him in ways that have become counterproductive to the changing historical picture his story might otherwise help develop. As part of this special issue on Bologne, this essay examines how exceptionality has framed Bologne and his Blackness in music-historical writing, and offers an alternative, approaching them as what Bruno Latour has termed “matters of concern.” I situate Bologne and his Blackness in an Atlantic view, looking beyond Paris to broaden and complicate the singular narratives monumentality has offered. Comparing his persona in Paris with that in 1770s and 1780s Cap-Français, the cultural hub of French-colonial Saint-Domingue, reveals how his persona was constituted through plural, shifting relationships between his musical virtuosity, amateurism, his body, and above all, his coloniality as a mixed-race Caribbean-born man. These relationships generate asymmetries and contingencies that resist the monolithic concepts of exceptionality relied on. Complicating the music-historical picture of Bologne, rather than resolving it to a clear, singular narrative, offers a path for Bologne’s story and his Blackness to productively rethink the historical picture scholars have aimed to write him into.